2009
DOI: 10.1007/s10551-010-0605-z
|View full text |Cite
|
Sign up to set email alerts
|

Deception in Business Networks: Is It Easier to Lie Online?

Abstract: deception, electronic communication, unethical behavior, computer networks, social networks, communication medium, issue moral intensity, moral intensity,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…Different lines of research have found richness and social presence to have significant effects on individuals' online behavior, including intention to use a website [1], online purchasing behavior [21], and even likelihood of deception in business email communication [12]. Hence, it is likely that phishing emails that vary in the amount of richness and presence cues are potentially more virulent-an issue that is particularly relevant given the increased sophistication of phishing emails.…”
Section: Introductionmentioning
confidence: 99%
“…Different lines of research have found richness and social presence to have significant effects on individuals' online behavior, including intention to use a website [1], online purchasing behavior [21], and even likelihood of deception in business email communication [12]. Hence, it is likely that phishing emails that vary in the amount of richness and presence cues are potentially more virulent-an issue that is particularly relevant given the increased sophistication of phishing emails.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, comparing to the physical world, in which humans have been living for thousands of years, the Internet is still a new and dynamic environment full of uncertainties and challenges for the majority. Furthermore, Logsdon and Patterson (2009) discovered that the Internet is a platform with higher risks for unethical communication and behaviour.…”
Section: Literature Searchmentioning
confidence: 99%
“…The theory is provocative, because the number of degrees of separation will be even fewer in select environments (Faber ). Indeed, the emergence of digitized social networks (Facebook, LinkedIn) increases the potential for an individual to either broadcast or target his/her dissatisfaction with a negotiating counterpart's behavior (Watts ; Logsdon and Patterson ). Therefore, our eighth proposition (P8) is that:
Proposition Eight : The more a counterpart is convinced that a negotiator is connected to the counterpart's social network, the less likely the counterpart will be to employ ethically ambiguous negotiation tactics.
…”
Section: A Framework For Understanding Counterparts' Ethical Motivationsmentioning
confidence: 99%
“…The theory is provocative, because the number of degrees of separation will be even fewer in select environments (Faber 2001). Indeed, the emergence of digitized social networks (Facebook, LinkedIn) increases the potential for an individual to either broadcast or target his/her dissatisfaction with a negotiating counterpart's behavior (Watts 2003;Logsdon and Patterson 2009). Therefore, our eighth proposition (P8) is that:…”
Section: Risks To Short-term Relational Interestsmentioning
confidence: 99%
See 1 more Smart Citation